Toxic leadership, social support and individual and organisational outcomes - Middleton, Sarah (My University, 2018)
Growing numbers of studies point to the negative impact and stress of Toxic Leadership (TL) on employees, both in their personal and work wellbeing. Such negatives include high levels of stress, reduced self-esteem and increases in alcohol and drug abuse. TL has also been found to reduce job satisfaction, organisational commitment behaviour and organisational citizenship behaviours. In addition, TL has been thought to result in severe health outcomes including; post-traumatic stress disorder, suicidal ideation and extreme forms of physical illness such as cancer and heart attacks. This South African study, based on a sample of 258 employees working across a wide range of industries, was conducted to explore Toxic Leadership and its effect on three dependant/outcomes variables. These outcome variables included Voluntary Turnover Intention, Work Engagement and Organisational Commitment Behaviour. In addition, Social Support and its role as a moderator was investigated. Consenting participants filled out six questionnaires namely; a Self-Developed Demographic Questionnaire, Schmidt’s Toxic Leadership scale (2008), Kantor’s (2013) Voluntary Turnover Intention (VTI) Scale, Utrecht Work Engagement Scale (UWES), Mowday, Steers & Porter (1979) Organisational Commitment Behaviour Questionnaire (OCQ) and Procidano and Heller’s (1983) Perceived Social Support Scale (PSI) (Adapted version). The results of the study indicated that Toxic Leadership was significantly correlated to the outcome variables. The simple regression also showed that Toxic Leadership raised levels of Voluntary Turnover Intention and lowered levels of Work Engagement, Organisational Commitment Behaviour and Social Support. While Social Support was directly related to the three dependant/outcomes variables with it having a positive effect on Work Engagement and Organisational Commitment Behaviour and decreasing levels of Voluntary Turnover Intention within the regressions. However, within the moderated multiple regressions, Toxic leadership relationship with Social Support actually had an inverse effect on the outcome variables. This is because instead of improving levels of Voluntary Turnover Intention, Work Engagement and Organisational Commitment Behaviour, it made negative effects of Toxic Leadership even worse. Some possible reasons for this was argued in this research. Finally, in addition to these findings, limitations and further contributions for future research into Toxic Leadership was also discussed.
A research report submitted in partial fulfillment of the requirements for the degree of Masters in Psychology by Coursework and Research Report in the field of Organisational Psychology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg on 15 March 2018
Keywords: Leadership--Moral and ethical aspects; Leadership; Management